APPLICATION OF AUDIO VISUAL MEDIA TO IMPROVE THE QUALITY OF FIQIH BOOK STUDY IN CLASS IIX 1 MA. AN NUR BANYUATES - Faurok, Mu’tazim (Jurnal Pendidikan Profesi Guru, 2025)
The use of media is very important for the learning process, because with the media it will be easier for students to understand the learning and help teachers to convey the material more easily. Audio visual media is one of the media that is accompanied by images and sound. The use of this media greatly helps teachers in developing learning techniques so as to achieve maximum learning goals. The purpose of this study is to implement and improve the quality of reading kitb in class IIX MA An.Nur students. This study applies Classroom Action Research (CAR) by carrying out four main steps. Based on the results of the study, the application of audio visual media can improve students' understanding and learning achievement with an average value of 71 in cycle I and increasing in cycle III by 78.